President Dr Shankar Dayal Sharma selected speeches - Sharma, Shanker Dayal (New Delhi India. M/o Information and Broadcasting.Publication Division, 2000)
This is the second volume of selected speeches of President Dr. Shankar Dayal Sharma. It is the compilation of his important speeches from January 1995 upto July 1997.
Contents: v.2. January 1995- July 1997
Keywords: Sharma, Shanker Dayal-Oratory; Speeches, addresses, etc; Festschriften